2017
DOI: 10.1038/srep40572
|View full text |Cite
|
Sign up to set email alerts
|

Differential cytotoxic effects of graphene and graphene oxide on skin keratinocytes

Abstract: Impressive properties make graphene-based materials (GBMs) promising tools for nanoelectronics and biomedicine. However, safety concerns need to be cleared before mass production of GBMs starts. As skin, together with lungs, displays the highest exposure to GBMs, it is of fundamental importance to understand what happens when GBMs get in contact with skin cells. The present study was carried out on HaCaT keratinocytes, an in vitro model of skin toxicity, on which the effects of four GBMs were evaluated: a few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
145
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(157 citation statements)
references
References 72 publications
11
145
0
1
Order By: Relevance
“…The size of GO sheets determines the toxicity and the inflammatory response in primary macrophages . On the same line, studies conducted on fibroblasts revealed that the cytotoxic potential of GNMs is mainly dependent on the oxidative state, with FLG being significantly less cytotoxic than GO . In primary neurons, exposure to GO and FLG causes very different effects on synaptic plasticity .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The size of GO sheets determines the toxicity and the inflammatory response in primary macrophages . On the same line, studies conducted on fibroblasts revealed that the cytotoxic potential of GNMs is mainly dependent on the oxidative state, with FLG being significantly less cytotoxic than GO . In primary neurons, exposure to GO and FLG causes very different effects on synaptic plasticity .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Human multiple myeloma cells (RPMI‐8226) treated with 50 μg ml –1 of GO for 24 hours caused minor variation in the morphology of the exposed cells (Wu et al, ). Similarly, the human skin keratinocyte cells (HaCaT) lost their morphology when exposed to GO at 50 μg ml –1 for 72 hours (Pelin et al, ). However, A549 cells exposed to GO at 200 μg ml –1 did not show any detectable changes in their morphology (Chang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…8 However, despite the importance of skin exposure and the dermotoxic potential of GBMs, very limited data on the cutaneous toxicity of these materials are currently available. Only few in vitro data regarding the effects on skin fibroblasts 9 and keratinocytes [10][11][12][13] are available, so far. In HaCaT skin keratinocytes, we previously demonstrated that FLG and GO reduced cell viability after interaction with plasma membrane.…”
Section: Introductionmentioning
confidence: 99%